The importance of ICT in English learning: indigenous students' perspectives / Fazyudi Ahmad Nadzri - Ahmad Nadzri, Fazyudi (UiTM Press, 2020)
The increasing dependence of people on technology nowadays is evident through the transformation of various sectors, placing ICT as an enabler in enhancing human capabilities and participations as a member of society. Policymakers and educators agreed that ICT is a supreme factor in leveraging positive effects on the students' achievements at large. Although myriad of studies have focused on ICT integration in education of students from the rural communities, the ICT issues among indigenous students have been sidelined. This study intended to address this gap by focusing on the views of indigenous students on the importance of ICT in learning English.